2009
DOI: 10.4141/cjss08004
|View full text |Cite
|
Sign up to set email alerts
|

Sheep camping influences soil properties and pasture production in an acidic soil of New South Wales, Australia

Abstract: This paper reports sheep camping influences on soil chemical and physical properties, and pasture dry matter (DM) production of an acidic soil on the southwest slopes of New South Wales, Australia. The experiment was conducted in the spring (October-November) of 2005 on a long-term field experimental site after 13 yr of rotational grazing. The factors considered were sheep camping (distance from the camping site), pasture type (perennial vs. annual pastures) and lime application (limed vs. unlimed treatments).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Quiroga et al (2009) reported that 10 yr of cattle grazing did not alter the soil P concentration in grazed and ungrazed treatments in Argentina. In contrast, Niu et al (2009) in Australia observed that soil P and K concentrations were greater in sheep-camping than in noncamping sites due to increased animal excreta. Catde and sheep grazing in pasture can result in similar or increased soil P and K concentrations compared with ungrazed land (Mathews et al, 1994;Abaye et al, 1997).…”
Section: Soil Phosphorus Potassium and Phmentioning
confidence: 74%
“…Quiroga et al (2009) reported that 10 yr of cattle grazing did not alter the soil P concentration in grazed and ungrazed treatments in Argentina. In contrast, Niu et al (2009) in Australia observed that soil P and K concentrations were greater in sheep-camping than in noncamping sites due to increased animal excreta. Catde and sheep grazing in pasture can result in similar or increased soil P and K concentrations compared with ungrazed land (Mathews et al, 1994;Abaye et al, 1997).…”
Section: Soil Phosphorus Potassium and Phmentioning
confidence: 74%
“…Quiroga et al (2009) reported that 10 yr of cattle grazing did not alter soil P concentration in grazed and non-grazed treatments in Argentina. In contrast, Niu et al (2009) in Australia observed that soil P and K concentrations were greater in sheep camping than in non-camping sites due to increased animal excreta. Cattle and sheep grazing in pasture can result in similar or increased soil P and K concentrations compared with non-grazing (Mathews et al, 1994;Abaye et al, 1997).…”
Section: Introductionmentioning
confidence: 84%
“…Similarly, Quiroga et al [47] observed that 10 years of cattle grazing did not alter soil P concentration in Argentina. In contrast, Niu et al [48] in Australia observed greater soil P and K concentrations in sheep camping than in non-camping sites due to increased animal excreta. Cattle and sheep grazing in the pasture can increase soil P and K concentrations compared to non-grazing [45].…”
Section: Effect Of (A) Cover Crop and (B) N Fertilization Rate On Soimentioning
confidence: 80%